Investigation of graphene layers on electrodeposited polycrystalline metals. (28th March 2016) - Nobili, L.; Magagnin, L.; Bernasconi, R.; Livolsi, F.; Pedrazzetti, L.; Lucotti, A.; Balijepalli, S.K.; Mezzi, A.; Kaciulis, S.; Montanari, R.
Abstract : Nowadays, many different methods are used to produce graphene. Electrochemical techniques represent a low‐cost and versatile route to deposit metals, although the characterization of graphene grown on electrochemically deposited polycrystalline metals is still in its infancy. In this work, several metal substrates were prepared by electrochemical processes and then covered with graphene layers grown by CVD. Free‐standing foils of Cu and Ni‐Cu alloy (20 wt.% of Cu) were prepared by electroforming, while a pure Ni film was obtained by galvanic displacement on a Si wafer. The thickness of Ni film on Si wafer was about 0.7 µm, whereas the Ni‐Cu foils were much thicker (12 µm). The characterization of the graphene films was performed by using Raman spectroscopy, XPS and AES. Copyright © 2016 John Wiley & Sons, Ltd.